Holding on by a thread: the continuing story of rotator cuff tears. (2021) - Ahmad, Zafar; Al-Wattar, Zaid; Rushton, Neil; Akinfala, Michael; Dawson-Bowling, Sebastian; Ang, Swee
Abstract : Rotator cuff tears are a common cause of shoulder pain. The incidence of these tears has increased significantly over the years, with the demands of an increasingly active elderly population. Therefore, a detailed understanding of rotator cuff tears will help doctors manage their patients' condition. This field has rapidly advanced over the past decade and this review provided an insight into the latest developments.